Motor competence assessment in physical education – convergent validity between fundamental movement skills and functional movement assessments in adolescence. (4th May 2023) - O'Brien, Wesley; Philpott, Conor; Lester, Diarmuid; Belton, Sarahjane; Duncan, Michael J.; Donovan, Brian; Chambers, Fiona; Utesch, Till
ABSTRACT: Background: The meaningful assessment of motor competence is well positioned for school-based curricular emphasis, through the integration of motor skills and movement patterns in both primary, and second level school physical education. Aligned with the growing interest in holistic motor competence assessment in physical education, the aim of this study was to assess the convergent validity between fundamental movement skills and functional movement assessments in a large cohort of adolescent youth. Method: A sample of 583 adolescents, aged between 12 and 16 years old participated in the study. Ten fundamental movement skills were assessed in line with the behavioural components from the Test of Gross Motor Development, and the Get Skilled Get Active resource. Seven specific functional movements were also assessed, using the existing protocol from the widely established Functional Movement Screen. All data were analysed using Bayesian procedures, in which the Bayes factors provided information about the probability of a hypothesis being true. Findings: The results indicate that it is very probable ( BF10  > 10, 000:1) that boys show higher actual motor competence levels in the object control subset of fundamental movement skills, when compared to girls. Moreover, a positive association between the total scores of the Functional Movement Screen and the locomotion subset of fundamental movement skills was found to be very probable ( BF10  = 7.737). Discussion: This study provides evidence of convergent validity between functional movement and fundamental movement skill assessments in adolescence. This study presents an evidence-informed rationale for physical education pedagogues to move beyond traditional perceptions of movement as being exclusively pertaining to physical skills, to a more holistic concept of motor competence comprising of both movement skills and movement patterns. Conclusion: The current study broadens the assessment perspectives of motor competence within physical education, by specifically heightening physical education teachers' awareness towards the possible complementarity of both locomotion and movement patterns in the psychomotor domain of adolescent learning in physical education.